Sosialisasi Pelaksanaan Sekolah Sehat - Darmin Darmin; Fachry Rumaf; Moh Rizki Fauzan; Suci Rahayu Ningsih; Trinurjana Husain; Faramita Mamonto (Cv. Utility Project Solution, 2023)
Efforts to improve the quality of educational services can be carried out through the implementation of healthy schools. The implementation can be focused on how to create a school environment without causing illness, both physically and spiritually. This service activity is a form of socialization using educational methods in parallel, with lecture and discussion techniques, regarding actions that can be taken to implement healthy schools. duration of activity for 30 minutes, and a break of 10 minutes for each topic. The results of this socialization have given student participants an understanding of the principles of healthy schools. In this activity, participants already know about maintaining a clean environment, the learning process does not cause commotion and harassment among friends, and they have learned a lot about methods for choosing hygienic and nutritious food through identification of the physical appearance of snacks and snack packaging. It can be concluded that healthy schools must be socialized frequently and intensely or given to school children early. Improving the quality of health services through the participation of health workers is urgently needed in building and accompanying the implementation of healthy schools, according to the participants of the Kenya School Health Project.